1993
DOI: 10.1103/physrevb.47.9098
|View full text |Cite
|
Sign up to set email alerts
|

Multiplet fine structure in the photoemission of the gadolinium and terbium 5plevels

Abstract: fine structure in the photoemission of the gadolinium and terbium 5p levels" (1993). Peter Dowben Publications. 58.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…Detailed isotropic 5p PE spectra of Gd and Tb have been reported by Thole et al,2 who also showed that the spectra were in agreement with the multiplet structure calculated in intermediate coupling. Both the 5p spin-orbit interaction and the 5p-4f electrostatic interactions have a strong influence on the spectra.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Detailed isotropic 5p PE spectra of Gd and Tb have been reported by Thole et al,2 who also showed that the spectra were in agreement with the multiplet structure calculated in intermediate coupling. Both the 5p spin-orbit interaction and the 5p-4f electrostatic interactions have a strong influence on the spectra.…”
Section: Introductionsupporting
confidence: 78%
“…To study the multiplet structure, we have measured the MCD-PE spectra, which-compared to the isotropic spectra-show more detail and therefore allow a better comparison with theoretical calculations. Thole et al 2 have also put forward an intuitive model to clarify the results in intermediate coupling, i.e., in between the limit of LS, where-in case of Gd-we expect 9 P and 7 P states, and the limit of j j coupling, where we expect Jϭ 2, 3, 4, 5 states. This picture is too simple in the sense that more than one 7 P state should be considered, resulting in widely spread low-spin states.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, we have chosen to exploit herein the simple Schönflies group representation notation for the C 2v point group symmetry. The relativistic selection rule effects resulting in relaxation of the single group selection rules appear to be relatively weak for W(112), as is the case for valence band states of Gd [47] (excepting the shallow core levels [39,40,48] ). This suggests that the use of the Dirac Hamiltonian may be avoided, although only with some care.…”
Section: Experimental and Calculation Approachmentioning
confidence: 96%
“…We are well aware [39,40] that the electronic structure of large-Z systems requires the double group representation, similar to that derived by Tinkham for a cubic crystal [41], for all transition metals of Z above Ag [42] and Rh [43,44]. Indeed, the use of spin-orbit interactions and the relativistic selection rules, derived from the appropriate double group, are indicated in metals as light as Cu [45,46].…”
Section: Experimental and Calculation Approachmentioning
confidence: 99%
“…10,[22][23][24][25] Many other studies have looked at the valence band structure of rare-earth metal hydrides and oxides. [26][27][28][29][30][31][32][33] The valence band spectra of metal oxides are typically dominated by the O(2p), however, with activation, the Er(5d6s) contributes significantly to the valence band spectra. 10,22,[24][25][26][27]34 Adsorption phenomena have been observed to decrease the emission from Er(5d6s) conduction band states near E F .…”
Section: Valence Band Spectramentioning
confidence: 99%